Refining the role of pms2 in Lynch syndrome: germline mutational analysis improved by comprehensive assessment of variants. Issue 8 (24th May 2013) - Borràs, Ester; Pineda, Marta; Cadiñanos, Juan; del Valle, Jesús; Brieger, Angela; Hinrichsen, Inga; Cabanillas, Ruben; Navarro, Matilde; Brunet, Joan; Sanjuan, Xavier; Musulen, Eva; van der Klift, Helen; et al.
Abstract : Background and aim: The majority of mismatch repair (MMR) gene mutations causing Lynch syndrome (LS) occur either in MLH1 or MSH2 . However, the relative contribution of PMS2 is less well defined. The aim of this study was to evaluate the role of PMS2 in LS by assessing the pathogenicity of variants of unknown significance (VUS) detected in the mutational analysis of PMS2 in a series of Spanish patients. Methods: From a cohort of 202 LS suspected patients, 13 patients showing loss of PMS2 expression in tumours were screened for germline mutations in PMS2, using a long range PCR based strategy and multiplex ligation dependent probe amplification (MLPA). Pathogenicity assessment of PMS2 VUS was performed evaluating clinicopathological data, frequency in control population and in silico and in vitro analyses at the RNA and protein level. Results: Overall 25 different PMS2 DNA variants were detected. Fourteen were classified as polymorphisms. Nine variants were classified as pathogenic: seven alterations based on their molecular nature and two after demonstrating a functional defect (c.538-3C>G affected mRNA processing and c.137G>T impaired MMR activity). The c.1569C>G variant was classified as likely neutral while the c.384G>A remained as a VUS. We have also shown that the polymorphic variant c.59G>A is MMR proficient. Conclusions: Pathogenic PMS2 mutations were detected in 69% of patients harbouring LS associated tumours with loss of PMS2 expression. In all, PMS2 mutations account for 6% of the LS cases identified. The comprehensive functional analysis shown here has been useful in the classification of PMS2 VUS and contributes to refining the role of PMS2 in LS.